2022
DOI: 10.1007/s12630-022-02218-z
|View full text |Cite
|
Sign up to set email alerts
|

Les canules nasales à haut débit comme traitement de première intention de l’insuffisance respiratoire hypoxémique associée à la COVID-19 : une étude de cohorte historique monocentrique.

Abstract: Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…This is in line with literature, where HFNO use has been shown to be effectively used in the wards in several studies, thus, reducing both the need for mechanical ventilation as well as transfers to the ICU for patients that could be treated with HFNO in the ward [4,18,24,25]. Importantly, HFNO use was not shown to increase COVID-19 infections in healthcare personnel when used both in an ICU and in a ward setting [4,26].…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with literature, where HFNO use has been shown to be effectively used in the wards in several studies, thus, reducing both the need for mechanical ventilation as well as transfers to the ICU for patients that could be treated with HFNO in the ward [4,18,24,25]. Importantly, HFNO use was not shown to increase COVID-19 infections in healthcare personnel when used both in an ICU and in a ward setting [4,26].…”
Section: Discussionsupporting
confidence: 88%
“…Orotracheal intubation rate was analysed in 22 studies [ 29 – 31 , 33 38 , 43 , 45 , 46 , 48 , 50 , 53 , 54 , 56 61 ], and in 12 of these studies, HFNC was associated with a reduction of orotracheal intubations. From these, five studies revealed that intubation rate was lower among those who were successfully managed with HFNC compared to those who failed it [ 29 , 37 , 59 ].…”
Section: Resultsmentioning
confidence: 99%